The Supreme Audit Institution in the role of improving the operation of the Ministry of Defense - Dionisijev, Ivan; Minovski, Zoran; Malchev, Bojan; Tocev, Todor (FACULTY OF SECURITY – Skopje, 2020)
The most important institution that regulates the national defense system in the Republic of North Macedonia is the Ministry of Defense, which in accordance with the Law on Defense creates the defense policy, determines the directions for the development of long-term and medium-term plans, manages human, material and financial resources. It is of great importance to providing support to the Army of the Republic of North Macedonia, which is a guardian of territorial integrity and sovereignty. Realizing its mission, the Army, apart from the Republic of North Macedonia, achieves the maintenance of peace and security outside the country through joint action or as part of collective security and defense systems. This paper explores the role of the Supreme Audit Institution (in our country the State Audit Office) in improving the legal and purposeful work of the Ministry of Defense, from the existence of the State Audit Office until today. Through detailed analysis of the audit reports issued by the State Audit Office for the Ministry of Defense in the last ten years, the total number of audits performed from 2010 to date is determined and identified the significant conditions regarding the financial operations of the Ministry, compliance with regulations and laws, as well other systemic weaknesses. For the analysis, all issued annual reports on the performed audits and the operation of the State Audit Office are used, as well as the last issued final audit report for the Ministry of Defense. In addition to analyzing those reports, the paper covers other literature and scientific papers on how the state audit affects the performance of the key institution in terms of defense and security.
Keywords: Ministry of Defense, Supreme Audit Institution, State Audit Office, Audit